Use and misuse of psychoactive medicines: a descriptive cross-sectional study in a densely populated region of Portugal - Ana Carmona Araújo; José Pedro Guerreiro; Carolina Bulhosa; Filipa Alves da Costa; João Goulão; Ana Paula Martins (Taylor & Francis Group, 2024)
Introduction Although psychoactive medicines (PMed) are needed in several psychiatric conditions, their use and misuse bear risks. We aimed at estimating the prevalence of PMed use and misuse.Methods Data on all PMed prescribed in 2017 and dispensed in community pharmacies of the Lisbon and Tagus Valley region of Portugal (ARSLVT) were extracted from ARSLVT medicines' dispensing database. For 21 PMed among prescription opioids, benzodiazepines and z-drugs (BZDR), antidepressants (AD) and anticonvulsants (AC), we estimated the number of users of each PMed, and assessed PMed misuse by a set of proxy indicators for studying this practice: chronic use (use of ≥180 DDD during the study period) of PMed intended for short-term treatments, concomitant use of several PMed, in particular if involving long-term (≥ 30 days) opioid analgesic (OA) use, and doctor shopping (patients consulting several physicians in order to have access to a quantity higher than intended by each prescriber). Data were analysed using descriptive statistics and hypothesis testing, and multivariate logistic regression was used to explore potential factors affecting long-term concomitant treatment of chronic OA with other PMed.Results PMed use prevalence was 21.7%: 6.6% for OA, 12.7% for benzodiazepines (BZD), 5.3% for AD and 2.8% for AC. BZDR were mainly prescribed in primary care and OA in hospital outpatients. Chronic use of PMed was observed in 25%, especially with sertraline and buprenorphine for opioid use disorder (long-term treatment), and lorazepam (short-term treatment). About 56.6% of OA chronic users were long-term concurrent users with other PMed, mainly BZDR. Risk of abuse was low for BZDR, whilst four opioids had meaningful doctor shopping indicators - fentanyl, opioid use disorder buprenorphine, morphine and hydromorphone.Conclusions BZD are the main PMed used in ARSLVT, often chronically, especially lorazepam. Prevalence of OA use is low, although with higher risk of misuse than BZDR. Concomitant use of several PMed is frequent.